Kajian Polifarmasi Terhadap Keamanan Obat Pada Pasien Geriatri - Jessy Dewi Awali; Pardilawati, Citra Yuliyanda; Soleha, Tri Umiana; Oktarlina, Rasmi Zakiah (CV. Jasa Sukses Abadi, 2024)
Geriatric patients an elderly patients suffering from a variety diseases (multimorbidity) caused by a decrease in body organ function. Multimorbidity in geriatric patients tends to lead to increased prescriptions and risks of polypharmacy. Polypharmacy can be defined as the use of five or more types of medications by a patient simultaneously. Polypharmacy is a major concern because of negative health impacts on patients, such as increased incidence of adverse drug reactions, harmful drug interactions, decreased medication adherence, and potentially inappropriate prescribing. Collaboration among doctors, pharmacists, other healthcare professionals, and families plays an important role in ensuring the effectiveness of treatment for geriatric patients, thus making the medications used safe and appropriate and reducing the negative impact of polypharmacy.